PERAN PERHIMPUNAN PELAJAR INDONESIA (PPI) DI AUSTRALIA DALAM MENANGGAPI FENOMENA BRAIN DRAIN - Muhammad Afriansyah Nasution Nasution; Arif Wicaksa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This study analyzes the role and strategy of PPI Australia in responding to the brain drain phenomenon. The escalation of the brain drain of skilled workers from Indonesia to Australia is driven by inequalities in the domestic employment ecosystem and the high appeal of welfare in the destination country. This human capital flight phenomenon threatens the resilience of national human resources. Amidst these dynamics, the Indonesian Student Association (PPI) in Australia occupies a strategic position as an intermediary forum for the student diaspora. The method used is descriptive qualitative with a case study approach. Data collection was conducted through in-depth interviews with PPI executives, representatives of the Indonesian Embassy (KBRI), and the student diaspora, supported by documentary analysis. The data were then examined using the foundations of the Constructivist Perspective, Diaspora Network Theory Theory, and Group Level of Analysis. The results show that PPI Australia addresses the brain drain pragmatically, acknowledging it as a rational individual choice stemming from structural limitations in Indonesia. The organization has repositioned its role from demanding physical repatriation to acting as a transnational catalyst focused on optimizing brain circulation and brain linkage. This strategy is implemented through career facilitation programs, knowledge dissemination (such as KIPI), the preservation of national identity (such as Pesta Rakyat), and collaborations with government and industry representatives. Although effective in maintaining emotional bonds and facilitating knowledge transfer, this organizational intervention faces structural limitations and remains palliative (a temporary relief). Ultimately, these measures have not been able to fundamentally stem the flow of the exodus as long as the allure of the Australian work ecosystem continues to outpace the readiness of domestic industries. Keywords: Brain Drain, Brain Circulation, Student Diaspora, Indonesian Student Association (PPI) Australia, Diaspora Network Theory.